USE OF HARMONIC SCALPEL IN LAPAROSCOPIC CHOLECYSTECTOMY - Zaidi, Abrar Hussain; Haleem, Abdul; Rana, Shabbir (Pakistan Armed Forces Medical Journal, 2011)
Objective: To determine the effectiveness and safety of the Harmonic Scalpel in laparoscopic cholecystectomy Study Design: Quasi Experimental Study. Place and duration of study: Surgical Unit -1 Combined Military Hospital Rawalpindi. From January to December 2009. Patients and Methods: A total of 110 consecutive patients undergoing laparoscopic cholecystectomy in which the procedures were performed exclusively with the Harmonic Scalpel were included. Patients were of either sex and of different age groups. Only three patients were operated in emergency and all other under went elective surgery. Ease of dissection and clarity of operative field [as determined by definition of dissection planes, need for using irrigation/suction and need for clearing the smoke by evacuation of gas], haemostasis and control of vascular pedicles, rate of complications, rate of conversion to open surgery and dissection time were analysed. Data was analyzed by SPSS. Frequencies and percentages were calculated Results: There were 65 females and 40 males. Age range was 24-72 years with mean age 45 years. Irrigation with saline and suction was needed in only 5 cases. There was practically no or minimal whitish smoke and none required evacuation of gas to clear the operative field from it. No patient had hemorrhage of any extent. Cystic artery was clipped in 40 (36.36%) patients and in all others [54.54%] it was secured by harmonic coagulation. None had CBD or bowel injury or post op sepsis. Two (1.82%) cases required conversion to open surgery due to dense adhesions and obscure anatomy. Cystic duct was dissected out with the same device but was clipped in all the cases. Average dissection time was 40 minutes (range, 17-75 minutes).There was no mortality. Conclusion: The Harmonic scalpel is safe and a surgeon friendly instrument for laparoscopic cholecystectomy.